Curving Performance Analysis of a Freight Train Transporting 50-Meter-long Rail Using Multibody Dynamics Simulation - Prasidya Wikaranadhi; Yunendar Aryo Handoko (Journal of Engineering and Technological Sciences, 2023)
Long rails are normally used in highspeed railways to minimize the number of rail joints and the dynamic impact force that follows. However, transporting long rails using a freight train requires multiple wagons for each rail section, presenting potential safety and loading gauge issues, especially when going through curves. Thus, a safety assessment needs to be done prior to actual transport. Computational simulation can be used for preliminary assessment. Finite element analysis can be used to incorporate the flexibility of the rails into the analysis but requires significant manpower and computer power to perform. In this study, an alternative method to model rail flexibility using a multibody approach is presented. The rails are sectioned into multiple rigid bodies along their length and interconnected using rotational joints. The stiffness coefficient of the joints is defined as a function of the actual rail’s physical properties. This modelling technique results in a simplified multibody model that retains the original rail elastic properties. Simulations of the constructed rail model hauled using a freight train were done and the results were compared to on-track test measurements of the same configuration. The comparison generally showed good agreement, showing this modelling technique’s ability and accuracy to simulate the case.